2016
DOI: 10.1007/s00438-016-1217-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression quantitative trait loci in long non-coding RNA PAX8-AS1 are associated with decreased risk of cervical cancer

Abstract: Paired box 8 (PAX8) is a crucial nephric-lineage transcription factor, and its aberrant expression has been detected in various types of cancer including Müllerian carcinomas. PAX8 antisense RNA 1 (PAX8-AS1), a potential regulator of PAX8, contains specific single nucleotide polymorphisms (SNPs) that may represent expression quantitative trait loci (eQTLs) for PAX8. In this study, we hypothesized that these eQTLs SNPs in PAX8-AS1 may influence the risk of cervical cancer. A case-control study of 1486 cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Recent reports showed that LINC00657 was induced by hypoxia in human endothelial cells and it might stimulate in regulating cell mitosis, DNA repair, and DNA replication [40, 41]. Previous studies identified two expression quantitative trait loci (eQTLs) SNPs located in lncRNA PAX8-AS1 that might influence the expression of target oncogene PAX8 and predict a decreased risk of cervical cancer [4244]. Additionally, KCNQ1OT1, which was one of the most upregulated lncRNAs in GA samples of our study, was also defined as an oncogene and it has been reported to have significantly higher expression levels in breast cancer and other types of malignant tumors [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showed that LINC00657 was induced by hypoxia in human endothelial cells and it might stimulate in regulating cell mitosis, DNA repair, and DNA replication [40, 41]. Previous studies identified two expression quantitative trait loci (eQTLs) SNPs located in lncRNA PAX8-AS1 that might influence the expression of target oncogene PAX8 and predict a decreased risk of cervical cancer [4244]. Additionally, KCNQ1OT1, which was one of the most upregulated lncRNAs in GA samples of our study, was also defined as an oncogene and it has been reported to have significantly higher expression levels in breast cancer and other types of malignant tumors [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an association between the rs2147578 polymorphism of lnc-LAMC2-1 and risk of childhood ALL has been demonstrated (6). There is limited information on the impact of PAX8-AS1 polymorphisms on cancer risk (19,24). Han et al (19) demonstrated that PAX8-AS1 rs4848320 and rs1110839 polymorphisms decreased the risk of cervical cancer, while Ma et al (24) reported that rs4848320 and rs1110839 were associated with prognosis of HCC in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA PAX8 antisense RNA 1 (PAX8-AS1) is mapped to chromosome 2q13 in the upstream region of PAX8 (19). An expression quantitative trait loci (eQTL) is a locus containing a genetic variant that influences the expression level of a gene (20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations